Analisis Kualitas Air Bersih di Wilayah Kerja Puskesmas Kepulauan Seribu Utara Berdasarkan Peraturan Menteri Kesehatan Nomor 32 Tahun 2017: Analysis of Clean Water Quality in the Work Area of the North Seribu Islands Health Center Based on the Regulation of the Minister of Health Number 32 of 2017 - Achmad Fadli (Indonesian Scholar Journal of Nursing and Midwifery Science, 2021)
Introduction: The availability of clean water is very important, given the very dynamic activities of people's lives. Residents living in coastal areas and small islands such as the Thousand Islands will find it difficult to get clean water for household purposes. The purpose of this research is to study the analysis of clean water quality in the working area of the North Seribu Islands Health Center based on the Minister of Health Regulation Number 32 of 2017. Methods: The method used in this study was qualitative research and research conducted through interviews conducted by several informants and secondary data analysis. The triangulation informants in this study were: 3 people officers and 1 community member. The validity test or data validity used in qualitative research is called triangulation, the triangulation used is the triangulation of data sources and triangulation of methods. Sources of data were obtained from secondary data at Seribu Utara District Health Center in the form of annual reports, in-depth interviews with informants, and direct observation. Results: Based on the results of research for the level parameters of dissolved solids are still high and still exist in some places it feels salty as well as for other parameters that are normal such as turbidity, temperature, air temperature, odor, and PH are still floating normally. normal. Suggestions to check regularly the quality of sanitary hygiene water at least once every 6 months. Discussion: Parameters of solute levels were still high and were still present in some salty terraces and other parameters were still normal such as turbidity, temperature, air temperature, odor, and pH were still on the normal threshold.